STRATEGI PENGEMBANGAN PRODUK KUE BASAH PADA USAHA MIKRO DI KAMPUNG KUE KOTA MALANG - Debora Gracia (Parsimonia - Jurnal Ekonomi dan Bisnis, 2015)
One of the marketing strategy that can be used for extening the product’s life cycle is product development strategy where the producer can create various product variants in order to always follow the market’s preference. The aim of this research is to analyze the implementation of product development strategy that is done by the cake micro entreprise in Kampung Kue, Malang city. This research was conducted on micro enterprises that have implemented the product development strategy by using qualitative method with in-depth-interview data collection. The result of this research shows that the three participants’ general strategy of product development implementation is by involving the counterparts that had been known firstly in order to evaluate the market’s response. The participants also prepare the alternative strategy in order to face whether the market’s response is good or bad. The reason of the participants implementing the product development strategies are caused by the ever- changing market’s preference, want to increase the profit and market share, and not wanting to be tied up with the relative price that is determined by market. The internal factors that noted in implementing the product development strategy are relation with consumer and the human resource’s ability that is owned, while the external factors that noted are the price and availability of raw materials, market’s demand, and competitors. The implications of this research are directed for the foods and beverages micro entreprise in order to keep control of product that have been launched into the market and expand the relationships with suppliers as well as for the government in order to conduct a training for the micro entreprises about the application of product development strategy.